CREATIVE ECONOMIC EMPOWERMENT THROUGH ECOPRINT TRAINING FOR PKK CADRES AS A DRIVER OF FAMILY ECONOMY IN SAYAR SUBDISTRICT TAKTAKAN SERANG - Ina Khodijah; Raden Irna Afriani; Yuliah Yuliah; Yollanda Octavitri (Yayasan Education and Social Center, 2021)
Program community service aims to initiate the creative economy of the community in the Village Sayar Taktakan District Serang city, especially for pkk cadres as the driver of the family economy. The program was held by a team of lecturers from the Faculty of Economics and Business, Bina Bangsa University. This form of program is to provide ecoprint training for pkk cadres of Sayar Village. The training started from the provision of materials about ecoprint, tips - tips to become an entrepreneur, recording financial statements in the family and business environment and a good way of speaking in establishing communication in business relations by a team of Lecturers bina bangsa university and Banten Shipping Polytechnic. then continued with the process of making ecoprint with several stages. The first stage is the mordanting process, the second stage is leaf treatment, the third stage is the process of leaf motif / leaf printing, the fourth stage is the steaming stage, the fifth stage is the color locking stage and the sixth stage is the final stage until the ecoprint results are ready for sale. The ecoprint training is to improve the skills of productive age PKK members in Sayar village berbasis creative economy. Through this ecoprint training is expected to be the birth of new female entrepreneurs to improve the family economy and to support their lives for the better in the future